Literasi Digital: Konvergensi Konten Promosi Usaha Mikro Kecil dan Menengah Sektor Kuliner - Baharuddin, Aris; Syarifuddin; Rizal S, Muh.; Akbal, Fatimah; Pratama, Aryan Agus (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Culinary SMEs in Makassar have significant economic potential, yet many struggle to adapt to digital marketing due to low digital literacy, limited content creation skills, and the absence of content convergence strategies. A needs assessment involving 50 SMEs confirmed these challenges and underscored the urgency of targeted digital capacity building. This program applied the Participatory Rural Appraisal (PRA) approach to ensure active involvement of participants in identifying needs, designing solutions, implementing training, and evaluating outcomes. Activities included workshops on social media management, creative content production, and integrated content distribution using CapCut, Canva, and Meta Business Suite. The program led to notable improvements: 85% of participants gained a better understanding of social media algorithms, 80% mastered Meta Business Suite for content convergence, and engagement rates increased from 2% to 5%. Promotional efficiency improved by 30%, accompanied by a 25% rise in digital sales conversion. PRA-based digital literacy training effectively strengthened the promotional capacity and competitiveness of culinary SMEs in the digital ecosystem. The program also contributed to the achievement of university Key Performance Indicators (IKU) through community engagement and academic output.